Quantification of stacking disordered Si–Al layer silicates by the Rietveld method: application to exploration for high-sulphidation epithermal gold deposits. (22nd April 2015) - Ufer, Kristian; Kleeberg, Reinhard; Monecke, Thomas
Abstract : Hydrothermally altered rocks hosting precious metal deposits frequently contain stacking disordered layer silicates. X-ray diffraction analysis using the Rietveld method can be used to determine mineral abundances in these rocks if suitable disorder models are applied. It is shown here that disorder models of kaolinite and pyrophyllite can be described by a recursive calculation of structure factors. This permits the physically sound refinement of real structure parameters of these disordered minerals and the determination of mineral abundances. Even mixtures containing two disordered Si–Al layer silicates can be quantified reliably. The developed disorder models can now be implemented in routine phase analysis, allowing the quantification of large numbers of samples to identify mineralogical gradients surrounding ore deposits.